Sonographic Pattern of Subacute Thyroiditis Is HLA-Dependent - Stasiak, Magdalena; Tymoniuk, Bogusław; Adamczewski, Zbigniew; Stasiak, Bartłomiej; Lewiński, Andrzej (Frontiers in Endocrinology, 2019)
Background: Since 1977 the susceptibility to SAT has been known to be HLA-B*35-related in approximately 70% of patients. Recently it has been demonstrated that SAT is associated with the presence of HLA-B*18:01 and DRB1*01, as well as with HLA-C*04:01. The association between the type of genetic SAT background and sonographic pattern of the disease has never been analyzed. The aim of the study was to evaluate the potential correlation between the presence of individual HLA haplotypes and the sonographic SAT pattern, and to provide the US characteristics of the analyzed SAT cases. Methods: HLA-A, -B, -C, -DQB1 and -DRB1 were genotyped using a next-generation sequencing method in 46 SAT patients. All patients were divided into the following groups according to the HLA haplotype: 1. HLA-B*35 and/or HLA-C*04, but without any other of the analyzed antigens; 2. HLA-DRB1*01, regardless of the co-presence of HLA-B*35 or C*04:01, but without HLA-B*18:01; 3. HLA-B*18 only, without any other of the analyzed antigens; 4. HLA-B*18:01 plus B*35, regardless of the presence of any other analyzed antigens. The US patterns of SAT thyroid lesions were compared among the groups. Results: The US image of SAT lesions in Groups 1 and 2 were similar. The typical SAT features for these groups were as follows: hypoechoic, strongly heterogeneous, bilateral, multiple areas, with decreased vascularization, usually oval with blurred margins, infrequently affecting the whole lobe or having nodule-like pattern. Several features of Group 3 were different from the other groups. In 60% of cases lesions were rather homogeneous, and in 100% - hypoechoic, in 80% of patients there was only one unilateral single SAT area filling the whole affected lobe. On the contrary to the other groups, in Group 4 no lesion was oval in shape. Conclusions: Our results provide for the first time the evidence that the US pattern of SAT lesions depends on HLA, and the determining factor is the presence of HLA-B*18:01. The deviations from the typical SAT US image are mostly pronounced in patients with the presence of only HLA-B*18:01, without any other analyzed haplotype. Further research is necessary to explain this phenomenon.